Influencia de la cantidad adicionada de vidrio de desecho en reemplazo de agregado fino, sobre la densidad, absorcion y resistencia a la compresion en morteros y pilas de albañileria - Contreras Laiza, Magali Maribel (2017)
One of the current global problems is environmental pollution, to counteract its effect on the ecosystem the following research proposes to use glass, non-degradable material naturally, as a substitute of fine aggregate in the percentages from 20 to 100% replacement in mortars of masonry units. In this research the physical and mechanical properties of a mortar made from a / c ratio of 0.45 was determined, a fine aggregate MF 2.0, cement type ICo and crushed glass with a MF of 2.33, according to different tests; determining the influence of the amount of waste glass replacement on the bulk density, percentage of water absorption and compressive strength in mortar and piles (raw masonry as E 0.70). It was determined that the minimum percentage absorption was 2.14%, the maximum compression resistance of 33.39 MPa, the minimum density of 1.97 g/cm3 and finally the results for compressive strength piles exceed the minimum of 3.4 MPa stipulated by the standard E 0.70 for 20% replacement glass sand. The increased resistance is due to the variety of sizes in the aggregate (fineness´ module acceptable as standard E 0.70) decreasing the amount of internal pores making a material more compact and also due to the increased adhesion by the angular shape of the particles of glass. The results obtained in this study confirm that the glass decreases the amount of water needed for the mixture without significantly affecting the compressive strength of mortar and pile configuration.